Exploring EFL Assessment Through Learners’ Perceptions - Naumoska Sarakinska, Biljana ("Blaže Koneski" Faculty of Philology, Skopje, 2020)
Although assessment is an integral part of the learning process, often, despite its significance, it is perceived in a negative light, causing many learners stress and anxiety. The questions that arise are why this is so, and how it can be resolved, i.e. how assessment can be brought closer to the learners so that they see it as a tool for their foreign language acquisition, development and improvement. The purpose of this paper is to take a closer look at Macedonian EFL learners’ perceptions of assessment, specifically the perceptions of freshmen and seniors majoring in English at the “Blaze Koneski” Faculty of Philology in Skopje, North Macedonia, as well as the factors that may affect how successful assessment is. It will also address what factors teachers need to consider when deciding on the method(s) of assessment to be used, with a special focus on teacher-, self-, and peer-assessment.
Keywords: teacher-/self-/peer-assessment, ESP